Pengaruh Media Sosial dan Brand Image Terhadap Customer Trust (Survei pada PT. SjJM Management Bandung) - Nuraeni, Nuri; Zahrah, Halimah; Sasangka, Indra (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The development of digital media has encouraged construction service companies to utilize social media and brand image to build customer trust. This study aims to analyze the influence of social media and brand image on customer trust at PT SJM Management Bandung. The research method used a quantitative approach with a survey technique of 30 respondents selected through purposive sampling. Data were collected using a 1–5 Likert scale questionnaire and analyzed using multiple linear regression with SPSS. The results showed that social media had no significant effect on customer trust (t=2.810; sig=0.09 > 0.05), while brand image had a positive and significant effect (t=2.774; sig=0.010 < 0.05). Simultaneously, social media and brand image significantly influenced customer trust (F=434.533; sig=0.000 < 0.05) with a contribution of 94% (R²=0.94). The study concluded that brand image is the dominant factor in building customer trust, while social media plays a supporting role in strengthening the company's image.